ANALYSIS OF RET-HE IN CHRONIC KIDNEY DISEASE PATIENTS AT DR.WAHIDIN SUDIROHUSODO HOSPITAL, MAKASSAR - Febrina Rovani; Asvin Nurulita; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Anemia, the common feature of Chronic Kidney Disease (CKD), is a multifactorial process due to disordered erythropoiesis and iron homeostasis. Determining the cause of anemia is important for adequate management. A bone marrow biopsy using Prussian Blue as the gold standard for diagnosis is invasive and more complicated to perform. Reticulocytes-Hemoglobin (Ret-He) a new parameter that indicates the hemoglobin content in reticulocytes is faster, easier, and less expensive. This study aimed to analyze the Ret-He in determining the iron status in patients with CKD. A cross-sectional study was held in the Clinical Pathology Laboratory of Dr. Wahidin Sudirohusodo Hospital Makassar during April-August 2016. Forty-five (45) samples were tested for iron serum (Fe), Total Iron Binding Capacity (TIBC), and Complete Blood Count (CBC) ordered by the physician. Reticulocytes-Hemoglobin was tested using the whole blood. Subjects were around the age of 19-71 years, no significant difference was found between numbers of males and females (46.6% and 53.3%). Hemoglobin median was 8 (5.0-15) g/dL, Fe 50 (6-177) U/mL, TIBC 183 (73-379), Transferrin Saturation (Tsat) 25 (5-95)%. Spearman correlation test method showed significant correlations between Ret-He and iron serum r=0.533, p <0.001, Ret-He and TIBC r=0.321 p=0.031 Ret-He and transferrin saturation r=0.416 p=0.019. The Mann-Whitney method showed no significant difference of Ret-He in both groups (Tsat <20% and >20%). There were significant correlations between Ret-He and iron, Ret-He and TIBC, Ret-He and transferrin saturation. A further study using larger samples is suggested to consider factors affecting the result of Ret-He.